Are clinicians' self-reported empathic concern and perspective-taking traits associated with their response to patient emotions?: Communication Studies. Issue 9 (September 2020) - Park, Jenny; Saha, Somnath; Han, Dingfen; Jindal, Monique; Korthuis, P. Todd; Moore, Richard; Beach, Mary Catherine
Highlights: Clinicians who report more empathic concern (EC) and perspective-taking (PT) traits did not focus more on patient emotions Clinicians who report more EC and PT tended to give information or advice in response to patient emotions Whether this specific clinician response is helpful to the patient is still unknown ABSTRACT: Objective: To understand whether clinicians' empathic concern and perspective-taking traits are associated with their response to patient emotions. Methods: We audio-recorded 41 HIV clinician interactions with 342 patients at two academic medical centers. We assessed clinicians' self-reported empathic concern and perspective-taking traits using the Interpersonal Reactivity Index and coded emotional communication using the Verona Coding Definitions of Emotional Sequences. We used random effects models to assess associations between clinician traits and clinician responses to patients' negative emotions, accounting for clustering of emotions within encounters and patients within clinicians. Results: Clinicians with more self-reported empathic concern received fewer emotional expressions from their patients (β -0.06; 95% CI -0.10, -0.01) and had greater odds of responding to emotions by giving information/advice (OR 1.10; 95% CI 1.01, 1.20). There were no associations between empathic concern or perspective-taking and any other clinician responses. Conclusion: Clinicians with higher levels of empathic concern respond to patient emotions by giving information and advice, a response traditionally thought of as a missed empathic opportunity, not by exploring emotions or providing empathy. Whether this is helpful to patients is unknown. Practice Implications: Clinicians should be aware of their tendency to give information to patients with emotional distress, and consider whether this response is helpful to patients.